Instrinsic Elements in Short Story the Gift of The Magi by O. Henry - Girsang, Martina; Sitio, Elizabeth; Surbakti, Natalia Br; Sihombing, Rachel M; Manullang, Maria Cinta A (Jurnal Riset Ilmu Pendidikan, 2025)
Literary works are defined as personal expressions of human thoughts, feelings, and experiences communicated through written or spoken form. These expressions serve aesthetic purposes and are classified into two main categories: fiction and nonfiction. Fiction encompasses a wide array of literary forms, including prose, poetry, and drama. Prose, in particular, is characterized by its free form, unbound by the constraints of poetic or song forms. Prose is generally used to convey stories, ideas, or information in a relaxed and natural way. In this article, the intrinsic elements of the selected short story analysis entitled The Gift of the Magi by O. Henry are analysis. The story is analysis in digital form and taken from a website on the internet. The descriptive qualitative method is used in the article to help interpret the elements found in the story. The study's findings indicate the presence of four notable intrinsic elements within the short story: plot, character, setting, and narrative perspective.